Molecular Cloning and Functional Characterization of Catalase in Stress Physiology, Innate Immunity, Testicular Development, Metamorphosis, and Cryopreserved Sperm of Pacific Abalone - Shaharior Hossen; Zahid Parvez Sukhan; Soo Cheol Kim; Md. Abu Hanif; Il-Keun Kong; Kang Hee Kho (MDPI AG, 2023)
Catalase is a crucial enzyme of the antioxidant defense system responsible for the maintenance of cellular redox homeostasis. The aim of the present study was to evaluate the molecular regulation of catalase (Hdh-CAT) in stress physiology, innate immunity, testicular development, metamorphosis, and cryopreserved sperm of Pacific abalone. Hdh-CAT gene was cloned from the digestive gland (DG) of Pacific abalone. The 2894 bp sequence of Hdh-CAT had an open reading frame of 1506 bp encoding 501 deduced amino acids. Fluorescence in situ hybridization confirmed Hdh-CAT localization in the digestive tubules of the DG. Hdh-CAT was induced by different types of stress including thermal stress, H2O2 induction, and starvation. Immune challenges with Vibrio, lipopolysaccharides, and polyinosinic-polycytidylic acid sodium salt also upregulated Hdh-CAT mRNA expression and catalase activity. Hdh-CAT responded to cadmium induced-toxicity by increasing mRNA expression and catalase activity. Elevated seasonal temperature also altered Hdh-CAT mRNA expression. Hdh-CAT mRNA expression was relatively higher at the trochophore larvae stage of metamorphosis. Cryopreserved sperm showed significantly lower Hdh-CAT mRNA expression levels compared with fresh sperm. Hdh-CAT mRNA expression showed a relationship with the production of ROS. These results suggest that Hdh-CAT might play a role in stress physiology, innate immunity, testicular development, metamorphosis, and sperm cryo-tolerance of Pacific abalone.